ANALISIS YURIDIS SANKSI PIDANA DALAM TINDAK PIDANA PENGANIAYAAN BERAT YANG DIRENCANAKAN TERLEBIH DAHULU (STUDI PUTUSAN NOMOR: 92/PID.B/2022/PN LBO): Juridical Analysis of Criminal Sanctions in Planned Serious Persecution Crimes (Decision Study Number: 92/Pid.B/2022/PN LBO) - R Sri Fajriah; Ermania Widjajanti (AMICUS CURIAE, 2025)
The O.R.O (Oorsprinkelijke Regins Onterwerp) doctrine defines abuse as acts causing injury and pain. Injury is when changes occur in the shape of a human body that differ from the shape of the body, whereas when it comes to understanding pain, changes in the shape of the body are not a prerequisite, only if they cause pain. A case of such abuse in Limboto, Gorontalo, was adjudicated under decision number 92/Pid.B/2022/PN.Lbo. For secondary data obtained through literature studies, and analyzed qualitatively by drawing conclusions deductively. It is concluded that the commission of severe persecution was premeditated on the penal punishment imposed by the court of judges against the accused under article 355 Paragraph (1) was proved but inadequate as a result of the abuse the victim died after several days of abuse. As a result of the death of such mistreatment, the writer to the accused should be subject to article 355 Paragraph (2) of severe abuse with a plan first that leads to death. In criminal penalties any criminal act must meet the purpose of identity, the penal punishment given to the defendant in this ruling the purpose of his confinement is not met, the imposition of Article 355 Paragraph (1) of the Criminal Code with a prison sentence of 10 years is not appropriate.